Species-level enterosignatures predict clinical phenotypes in chronic hepatitis B and causal triangulation of gut-metabolite-CHB interactions - Yuan, Tingting; Chen, Jiali; Yang, Jing; Li, Lianfeng; Lu, Shan; Pu, Ji; Sun, Yamin; Lin, Wenchao; Lu, Yubin; Zhu, Zhaoqin; Zheng, Han; Xu, Jianguo (Frontiers in Microbiology, 2025)
Chronic hepatitis B (CHB) remains a significant global health challenge, with research indicating the gut microbiota’s influence on disease progression, although investigations have primarily been limited to the genus level. This study conducted species-level research using the Human Gut Microbiome Analysis Database (HGMAD) to examine differences in gut microbiota between CHB patients and healthy controls (HC), to investigate enterotype associations with CHB, to assess the predictive capacity of enterosignatures for CHB phenotypes, and to determine causal relationships among gut microbiota, metabolites, and CHB. The cross-sectional investigation included 129 CHB patients and 58 HC, with fecal samples analyzed by 16S rRNA gene sequencing of the V3–V4 region. Significant differences in α-diversity and β-diversity (P < 0.05) were observed between the CHB and HC groups. Taxonomic analysis revealed that the high prevalent bacteria group was lower in CHB patients (61.15%) than in HC (98.05%), indicating increased gut microbiota heterogeneity in CHB. Among known bacterial species, pathogens showed higher prevalence in CHB patients (22.80% vs. 11.49%), with several potential enteropathogenic bacteria (e.g., Bacteroides fragilis and Haemophilus parainfluenzae) enriched in CHB. Dimensionality reduction and clustering analysis of gut microbiota in CHB patients revealed two distinct enterotypes: ET-P dominated by Prevotella and ET-B dominated by Bacteroides. ET-P demonstrated a correlation with elevated levels of hepatitis B virus (HBV) DNA, hepatitis B surface antigen (HBsAg), hepatitis B e antigen (HBeAg), CD4+T-cell count and CD8+T-cell count, and alpha-fetoprotein (AFP). The enterosignatures of ET-P and ET-B effectively predicted key clinical indicators: the area under the curve (AUC) was 0.78 (95% confidence interval [CI]: 0.69–0.86) for HBeAg levels, 0.86 (95% CI: 0.79–0.93) for HBV DNA levels, 0.75 (95% CI: 0.65–0.84) for AFP status, and 0.85 (95% CI: 0.77–0.92) for CD4+T-cell count status. Mendelian randomization (MR) analysis, integrating two gut-microbiota databases, provided genetic evidence for causal relationships between 16 species-level gut microbes and CHB. An elevated abundance of Prevotella copri was associated with an increased risk of CHB (OR = 1.42, 95% CI: 1.01–2.00, P = 0.045). Additionally, mediation MR analyses revealed potential metabolite-mediated mechanisms underlying the role of gut microbiota in CHB. Two enterotypes were identified in CHB patients, ET-P demonstrated positive associations with HBV activity and viral load. The enterosignatures derived from both enterotypes effectively predicted key CHB clinical indicators, establishing causal links and potential underlying mechanisms between gut microbiota and CHB. These findings indicate that the gut microbiota maintains close connections to HBV infection, correlating with viral load, host immune status, and disease prognosis in hepatitis B.